EFL Teacher’s View on Virtual Based Storytelling in Teaching Vocabulary for Elementary Students - Dila Jessica Neolaka; Risa Fitria; Ika Kana Trisnawati (ACCENTIA: Journal of English Language and Education, 2021)
Teaching English to young learners (TEYL) is different from teaching adults. Children need constant attention and assistance as well as motivating methods to keep them engaged particularly during online learning in the pandemic era these days. This study aims to investigate English teacher’s perception on teaching English vocabulary to elementary students’ by using storytelling method in a virtual environment. The study asked the following question: What is the English teacher’s perspective on teaching English using storytelling virtually during the pandemic? The study interviewed an English teacher of a private school in Bekasi, Indonesia using a semi-structured interview guide. The study found that the English teacher agreed that storytelling is beneficial to use in teaching English for young learners. In addition, the teacher mentioned that there were several issues during the online learning such as unenthusiastic students, students’ limited access to the gadgets, and students’ passive involvement during the learning. Further, in terms of teaching with storytelling, the teacher would request the students to make a video and retell stories in the textbook. This study concludes that it is paramount for English teachers to continuously provide varied teaching methods in order to solve problems faced by Indonesian elementary students during online learning.